Popular passive dampers for structural control: A review - Ghosh, Aparna Dey; Konar, Tanmoy (Journal of Structural Engineering, 2024)
Passive dampers encompass a range of non-power consuming devices that can be utilized for the mitigation of structural vibration induced by external excitation, such as wind, earthquake, sea waves, and traffic. Common types of passive dampers include friction dampers, fluid viscous dampers, viscoelastic dampers, metallic dampers, tuned mass dampersand tuned liquid dampers. Considering the relative ease of design and installation, as well as the requirement of low initial and maintenance costs, passive dampers hold tremendous potential in providing a sustainable solution to the challenge of structural protection from environmental loading. The development of passive energy dissipation devices for civil engineering structures is a fast-expanding field with significant recent progress. This paper presents a stateof-the-art review of some of the more established passive dampers used for controlling structural vibration. Working mechanisms, design philosophies, advantages and shortcomings of these dampers are discussed. The applicability of the devices is also highlighted, along with a summary of their installations in real-life structures.